2016
DOI: 10.1520/acem20150035
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Cementitious Systems: Formation Factor Determination and the Influence of Conditioning Procedures

Abstract: The number of people wanting to use electrical tests to determine the transport properties of concrete has increased with advancements in the portability of hand-held testing devices. Electrical measurements are an attractive test method to quantify transport properties of cement-based materials since they can be performed rapidly. There is a high potential for using these tests in quality control or mixture qualification. However, electrical measurements can be significantly influenced by curing and storage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Previous work has demonstrated how finite layered effects can influence surface and bulk electrical measurements in different ways: half-space [44], or finite slab geometries [11,45–47]. One approach to investigate the effects of layered materials is to study the ratio of surface resistivity to uniaxial resistivity, as originally described by Morris et al [40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has demonstrated how finite layered effects can influence surface and bulk electrical measurements in different ways: half-space [44], or finite slab geometries [11,45–47]. One approach to investigate the effects of layered materials is to study the ratio of surface resistivity to uniaxial resistivity, as originally described by Morris et al [40].…”
Section: Resultsmentioning
confidence: 99%
“…If leaching occurs, as illustrated in Figure 1, the pore solution concentration (and resistivity) can change by a significant factor as ions migrate from the specimen into the surrounding storage solution. In a study by Spragg [11], this was shown, for the concrete considered, to be a factor of four. In this paper, experiments and modeling are combined to provide insights into the significance and magnitude of the influence of leaching on electrical properties measured in standardized tests.…”
Section: Research Significancementioning
confidence: 98%
See 3 more Smart Citations